KAJIAN KEMAMPUAN AKAR TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) DALAM MENYERAP LOGAM MERKURI PADA TANAH TERCEMAR - Khairuddin Khairuddin; Rismawaty Sikanna; Sabaruddin Sabaruddin (KOVALEN: Jurnal Riset Kimia, 2017)
The Research has done on assessment ability plants of kale land root’s (Ipomoea reptans Poir) in absorbing metallic of mercury (Hg) on polluted soil. Methods of assessment done by complete randomized design (CRD) to determine the influence of plant age and concentration of the planting medium to large concentrations absorbed of mercury in plant roots. Age of planting consists of 4 harvest time, it is 2, 3, 4, and 5 weeks. The concentration of the cultivation medium is 25 ppm, 50 ppm, 75 ppm dan 100 ppm. The results of analysis variance test for the effect of cultivation age indicate the real difference (F calculation > F 5 %), where the test results of BNT 0,05 obtained in the third week is the maximum age of planting. The influence of concentration on analysis variance test and LSD analysis indicate the real difference, where F calculation > F 1%.Keywords: Absorption, Metal Mercury, Land Plants kale, Age of planting, growing media concentration.